Turmeric - maize and onion intercropping systems. III. Nutrient uptake - PALANIAPPAN, K SIVARAMAN, S P (Journal of Spices and Aromatic Crops, 1996)
Experiments were conducted at Bhavanisagar and Coimbatore (Tamil Nadu, India) to determine uptake of nutrients as influenced by intercropping systems with turmeric (Curcuma langa) - maize (Zea mays) and onion (Allium cepa), and to study nitrogen uptake pattern by various plant parts of turmeric in such situations. The results revealed that nutrient uptake by the intercropping systems was higher than the uptake of either of the sole crops of turmeric, maize and onion. The total uptake of nitrogen by various intercropping systems varied from 61 to 80 per cent more than the uptake of nitrogen by the sole crop ofturmeric at Bhavanisagar and 57 to 77 per cent at Coimbatore. Similarly it varied from 82 to 104 per cent more than the sole crop of maize at both the locations. A similar result was obtained in onion also. Similar trends were observed in uptake of phosphorus and potassium in the intercropping systems. The results indicated that for sustainable production of intercropping systems, meeting the combined nutritional requirements of component crops is essential.